Reactive polymers bearing styrene pendants through selective anionic polymerization of 4-vinylbenzyl methacrylate - Mohan, Y. Murali; Raghunadh, V.; Sivaram, S.; Baskaran, D. (Macromolecules, 2012)
Selective anionic polymerization of 4-vinylbenzyl methacrylate at methacrylate site has been achieved using resonance stabilized anionic initiators such as 1,1-diphenylhexyllithium (DPHLi) and tritylpotassium (TritylK) in tetrahydrofuran (THF) at -78 degrees C. Polymerization proceeded selectively through methacrylate functionality of the monomer in a controlled manner and produced polymers and copolymers with narrow molecular weight distribution at low temperatures (<=-40 degrees C). H-1 NMR of the polymer showed the presence of styrene pendants in every monomeric repeating unit. The polymerization results confirm that the resonance stabilized carbanions with an optimum pK(a) (30 <= pK(a) <= 32) of their conjugate acids such as DPHLi and TritylK do not react with styrene functionality at 78 degrees C. The selective initiation without cross-linking is attributed to the differences in the electronegativity between polar methacrylate and styrene functionalities and an attenuation of initiator reactivity at low temperature. Poly(4-vinylbenzyl methacrylate) and its copolymers with the vinyl pendant in close proximity with ester linkage are very reactive and unstable, readily undergoing cross-linking in solution or in solid state with or without a radical initiator.